Improving of Agricultural Technologies for Growing Jerusalem Artichoke (Helianthus Tuberosus l.) in Uzbekistan. - EliyorKh. Berdimuratov, AbduganiА. Elmurodov (International Journal of Advanced Science and Technology, 2020)
In the context of Uzbekistan, early growth rates for new varieties such as Mujiza and Etirof were studied, as well as the productivity of new varieties of artichoke.There were generated agricultural techniques of planting early spring and late-autumn varieties as separate feed for livestock and agro-techniques of individual growing for the food and pharmaceutical industry were also developed. Considering the high inulin yield in tuber, which grows in the mountainous and foothill areas of the republic, it is advisable to grow both annual and perennial crops for the food and pharmaceutical industry, as well as on the lowlands for the livestock industry.